If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2(x + 4) = 2x + -3 Reorder the terms: 3x + -2(4 + x) = 2x + -3 3x + (4 * -2 + x * -2) = 2x + -3 3x + (-8 + -2x) = 2x + -3 Reorder the terms: -8 + 3x + -2x = 2x + -3 Combine like terms: 3x + -2x = 1x -8 + 1x = 2x + -3 Reorder the terms: -8 + 1x = -3 + 2x Solving -8 + 1x = -3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -8 + 1x + -2x = -3 + 2x + -2x Combine like terms: 1x + -2x = -1x -8 + -1x = -3 + 2x + -2x Combine like terms: 2x + -2x = 0 -8 + -1x = -3 + 0 -8 + -1x = -3 Add '8' to each side of the equation. -8 + 8 + -1x = -3 + 8 Combine like terms: -8 + 8 = 0 0 + -1x = -3 + 8 -1x = -3 + 8 Combine like terms: -3 + 8 = 5 -1x = 5 Divide each side by '-1'. x = -5 Simplifying x = -5
| 5x+-5=20 | | 8W+2W-7=23 | | 7+4x-4t=-11 | | 19x-13=25 | | 8x-2+3x=5x+10 | | (2+(2-(2+(2-(2+r)))))=1 | | -7y-2=-6y-6 | | 3(2+5x)+3=2(1-3x) | | 2x+3(1x-10)=45 | | (x^2+1)= | | 2x+3(x-10)=-45 | | y=-0.2*x+520.4 | | 1x-5(x+2)=26 | | 6*6+7= | | 2sen^2x-senx-1=0 | | 5/678 | | 5/6.35 | | 5/6•35 | | 2y-50+5y-17=180 | | 3=5-3/4 | | 5x-8(x+5)= | | 3x(x+0)=0 | | 1/3,4 | | 2x+3=-(x+1) | | 3(k-6)-(-3k-8)=5k | | 35,5/6 | | rs-6r+st-6t= | | y=2x+6(6*7) | | 0=3y^2+30y+70 | | 5(n+2r)+3n= | | 0.3+0.6=1.5 | | 5x-3-2x=x+11 |